Efficient posterior exploration of a high‐dimensional groundwater model from two‐stage Markov chain Monte Carlo simulation and polynomial chaos expansion. Issue 5 (28th May 2013) - Laloy, Eric; Rogiers, Bart; Vrugt, Jasper A.; Mallants, Dirk; Jacques, Diederik
Key Points Efficient two‐stage MCMC simulation for CPU‐demanding sampling Real‐world application to the inference of a multi‐layered 3D aquifer model A 2‐5 times observed speed up in sampling efficiency